Neuronal dynamics of flexible motor control in the human subthalamic nucleus and cortex - Fischer, P (2017)
Beta and gamma oscillations have long been associated with motor control, with beta generally assumed to be anti-kinetic and gamma pro-kinetic. This thesis aims to link these oscillations to several components of flexible motor control: inter-limb coordination, sensorimotor synchronization, abrupt stopping and regulation of the extent and speed of muscle contractions. The subthalamic nucleus (STN) plays an important role in controlling movements. In three separate experiments, I recorded local field potentials from the STN in Parkinson’s disease patients on dopamine replacement therapy after they underwent deep brain stimulation surgery. In one task, EEG recordings were also obtained from healthy participants. In a stepping-in-place paradigm, STN beta oscillations were modulated relative to the contralateral step cycle, indicating segregated processing of the left and right limb in the contralateral STN at beta frequencies. Beta modulation was enhanced when auditory cues were provided and sensorimotor synchronization improved. During rhythmic finger tapping and sudden stopping, beta oscillations were again modulated. If post-movement beta was relatively high shortly before participants heard the stop signal, stopping was more successful. I hypothesize that post-movement beta reflects either evaluation of the motor plan according to sensory feedback from the last finger tap or processing related to timing adjustments in the next movement. In both cases, low post-movement beta suggests active neural processing and less reserve for stopping. The main correlate of successful stopping during the actual inhibition process directly following the stop signal, however, was a gamma power increase. Finally, both gamma and beta oscillations were modulated during motor imagery of three different force levels, indicating that their levels reflect motor vigour even in the absence of proprioceptive feedback and may be used as neurofeedback or BCI control signal. Altogether, these findings suggest that beta oscillations reflect wider motor control functions than just being anti-kinetic. Conversely, STN gamma oscillations do not only have a pro-kinetic role, as widely perceived, but are important for abrupt action stopping as well.